Tracking the Filling, Outburst Flood and Resulting Subglacial Water Channel From a Large Canadian Arctic Subglacial Lake - Laurence Gray; Benoît Lauzon; Luke Copland; Wesley VanWychen; Christine Dow; Will Kochtitzky; Karen E. Alley (Geophysical Research Letters)
Abstract We use digital elevation models (DEMs) and ICESat‐2 data to study the filling and outflow from a large subglacial lake under Manson Icefield in the Canadian Arctic. When full, the lake is ∼17 × 3 km with an area of 52 km2. Early in 2021 the ice surface over the center of the lake sank by >140 m implying a subglacial outburst flood of ∼4 km3. Rapid outflow occurred over ∼30 days at an average rate of ∼1,500 m3s−1 resulting in the formation of a single ∼15 km subglacial outflow path detectable from post‐outflow surface depression. The shape of the surface depression, 600–800 m wide by 2–4 m deep, reflects the shape of the subglacial channel prior to closure. Downstream ice movement appears unaffected by the outflow. After outflow ends the surface depression persisted over weeks, apparently dependent on the difference between water and overburden pressures.